Uncovering the role of DICER and pericentric heterochromatin expression during spermatogenesis - Yadav, Ram Prakash (fi=Turun yliopisto|en=University of Turku|, 2020)
Male germ cell differentiation is a complex process that includes mitotic proliferation, meiosis and haploid differentiation phase, during which the cell undergoes dramatic morphological changes to produce mature spermatozoa. Male germ cells have unusually diverse transcriptomes that include a broad variety of protein-coding mRNAs and their isoforms, but also a considerable number of noncoding RNAs (ncRNAs). This research focuses on a specific type of ncRNAs, major satellite repeat (MSR) transcripts that originate from the pericentric heterochromatin regions of the chromosomes and their interplay with the endonuclease DICER during mouse spermatogenesis. Using a germ cell-specific Dicer1 knockout mouse model, I showed that DICER is essential for spermatogenesis and male fertility. The deletion of Dicer1 mainly affected haploid male germ cell differentiation and resulted in defective chromatin condensation and nuclear shaping of spermatids, leading to severe oligoasthenoteratozoospermia and infertility. I revealed that MSRs are transcribed during normal spermatogenesis, particularly in meiotic spermatocytes. Interestingly, MSR transcripts were shown to be aberrantly induced in DICER-null spermatocytes. Only those transcripts that originate from the forward strand of MSR DNA were misregulated in the absence of DICER, suggesting a strand-specific function for DICER in vivo. The forward MSR transcripts and DICER were localized to both the cytoplasm and the nucleus, where nuclear DICER was specifically associated with pericentric heterochromatin regions of chromosomes. Moreover, I showed that MSR transcripts are found in complexes with DICER in the testis, and their processing into small RNAs is compromised in Dicer1 knockout mice leading to an elevated level of forward MSR transcripts in meiotic cells. I also provided evidence of epigenetic imbalance of the pericentric heterochromatin and meiotic chromosome missegregation in Dicer1 knockout testes. These results clearly illustrate that DICER is essential for male fertility, and it contributes to the regulation of pericentric heterochromatin during spermatogenesis by direct targeting MSR transcripts. Furthermore, these studies strongly suggest that the expression of pericentric heterochromatin may have a functional role in the regulation of male germ cell differentiation and fertility.

DICER ja perisentromeerisen heterokromatiinin ilmentyminen spermatogeneesin aikana Spermatogeneesissä sukusolut jakautuvat meioottisesti ja erilaistuvat haploideiksi hedelmöityskykyisiksi siittiöiksi. Tämän prosessin aikana ne ilmentävät genomiaan laajasti, ja proteiineja koodaavien RNA:iden lisäksi niiden transkriptomi koostuu myös huomattavasta määrästä ei-koodaavia RNA:ita. Tässä tutkimuksessa keskityttiin tiettyihin ei-koodaaviin RNA-molekyyleihin, jotka ovat peräisin kromosomien perisentromeerisella heterokromatiinialueella sijaitsevista satelliittitoistojaksoista (major satellite repeats, MSR). Erityisesti tutkimuksessa selvitettiin DICERendonukleaasin toimintaa MSR-RNA:iden säätelyssä hiiren spermatogeneesin aikana. Käyttämällä poistogeenistä Dicer1-hiirimallia osoitin, että sukusolujen DICER-proteiinilla on keskeinen merkitys hedelmällisyyden ylläpidossa, sillä Dicer1-geenin poistaminen esti normaalin siittiötuotannon. Varsinkin haploidi erilaistumisvaihe häiriintyi, mikä johti rakenteeltaan epänormaalien siittiöiden muodostukseen. Tutkimukseni paljasti, että MSR-RNA:ita tuotetaan spermatogeneesin aikana etenkin meioottisissa sukusoluissa, ja että Dicer1-poistogeenisen hiiren sukusoluissa MSR-RNA:iden määrä oli huomattavasti kohonnut. Tulosteni mukaan MSR-RNA:t ja DICER sijaitsivat sekä solulimassa että tumassa, ja näytin DICER-proteiinin sitoutuvan perisentromeerisille heterokromatiinialueelle. Lisäksi osoitin, että kiveksessä DICER ja MSR-RNA-molekyylit löytyvät samoista komplekseista, ja että Dicer1-poistogeenisessä hiiressä MSR-RNA:iden prosessointi oli häiriintynyt. Tämä viittaa siihen, että DICER säätelee MSR-RNA-molekyylejä osallistumalla niiden prosessointiin. Lopuksi osoitin, että Dicer1-geenin poistaminen sai aikaan muutoksia sukusolujen heterokromatiinin epigeneettisessä tilassa. Lisäksi Dicer1-geenin poistaminen oli yhteydessä meioottisten jakautumisten häiriöihin ja aneuploidiaan, mikä mahdollisesti johtuu häiriöistä perisentromeerisen heterokromatiinin toiminnassa. Kaiken kaikkiaan tutkimukseni tulokset osoittavat, että DICER-proteiinilla on keskeinen rooli miesten sukusolujen erilaistumisessa ja MSR-RNA:iden säätelyssä. Tulokset myös viittaavat siihen, että perisentromeerinen heterokromatiini on toiminnallisesti tärkeää normaalin siittiötuotannon ja hedelmällisyyden kannalta